Respuesta :

Answer:

one solution; the answer is -3 = x

Step-by-step explanation:

Answer:

Step-by-step explanation:

Simplifying

5 + -2x = 4 + -2x + 4 + x

Reorder the terms:

5 + -2x = 4 + 4 + -2x + x

Combine like terms: 4 + 4 = 8

5 + -2x = 8 + -2x + x

Combine like terms: -2x + x = -1x

5 + -2x = 8 + -1x

Solving

5 + -2x = 8 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.

5 + -2x + x = 8 + -1x + x

Combine like terms: -2x + x = -1x

5 + -1x = 8 + -1x + x

Combine like terms: -1x + x = 0

5 + -1x = 8 + 0

5 + -1x = 8

Add '-5' to each side of the equation.

5 + -5 + -1x = 8 + -5

Combine like terms: 5 + -5 = 0

0 + -1x = 8 + -5

-1x = 8 + -5

Combine like terms: 8 + -5 = 3

-1x = 3

Divide each side by '-1'.

x = -3

Simplifying

x = -3